The Land is Waiting: Looking for Movements Toward Indigenous-led Conservation in Northern Alberta - Hoek, Lindsay Vander (2021)
This paper demonstrates the increasing recognition and need for Indigenous Protected and Conserved Areas (IPCAs) in Canada, for reasons related to biodiversity protection, reconciliation, and cultural connection. While awareness of this need is increasing at a national level, this paper questions whether themes found and suggested by the 2018 Indigenous Circle of Experts Report We Rise Together are present in Northern Alberta conserved and protected areas. A conceptual framework is developed using themes from the national Indigenous Circle of Experts Report and literature, highlighting the need for Indigenous leadership, and for Western style protected area management to create the space for Indigenous leadership and Traditional Knowledge in the care of conserved and protected areas. The conceptual framework uses themes of Ethical Space and Paradigm Shift to analyze four representative case studies of conserved and protected areas in Northern Alberta, determining whether indicators of these themes are present. Findings demonstrate that there are movements toward creating Ethical Space within Western structures, indicated through acknowledging Treaty, nation to nation relationships, and the recognition and need for cultural competency training for non-Indigenous staff. Limited results are found regarding the theme Paradigm Shift, which looks for indications of whether the wilderness paradigm is present, for the inclusion of traditional human activity, and for equality of knowledge systems within management of conservation and protected areas. While indicators of Ethical Space and Paradigm Shift are found in Northern Alberta, this paper suggests further research to demonstrate whether the experience of First Nations and Métis people corroborate the findings of each case study.